2019
DOI: 10.2147/ott.s220730
|View full text |Cite
|
Sign up to set email alerts
|

<p>Proton Therapy For Lymphomas: Current State Of The Art</p>

Abstract: The combination of brief chemo-radiotherapy provides high cure rates and represents the first line of treatment for many lymphoma patients. As a result, a high proportion of long-term survivors may experience treatment-related toxic events many years later. Excess and unintended radiation dose to organs at risk (particularly heart, lungs and breasts) may translate in an increased risk of cardiovascular events and second cancers after a few decades. Minimizing dose to organs at risk is thus pivotal to restrain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
3
7
0
Order By: Relevance
“…The mean OAR doses for the PBT plans in our patients were comparable with those of previous studies, 11 , 28 , 30 but our photon RT doses were lower than in other studies. For example, the average MHD, MLD, and MBD for photon RT in our study was 9.5 Gy, 7.9 Gy, and 2.5 Gy, respectively, but a recent review of 16 studies in patients with mediastinal HL reported an average MHD, MLD, and MBD of 11.4 Gy, 9.4 Gy, and 4.4 Gy, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean OAR doses for the PBT plans in our patients were comparable with those of previous studies, 11 , 28 , 30 but our photon RT doses were lower than in other studies. For example, the average MHD, MLD, and MBD for photon RT in our study was 9.5 Gy, 7.9 Gy, and 2.5 Gy, respectively, but a recent review of 16 studies in patients with mediastinal HL reported an average MHD, MLD, and MBD of 11.4 Gy, 9.4 Gy, and 4.4 Gy, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…This is particularly beneficial for patients with relapsed disease who have already received RT as it may lower the risk of acute cord and bone marrow toxicities as well as risk of radiation pneumonitis. 29 The mean OAR doses for the PBT plans in our patients were comparable to previous studies 11,28,30 , but our photon-RT doses were lower than in other studies. For example, the average MHD, MLD, and MBD for photon-RT in our study was 9.5 Gy, 7.9 Gy and 2.5 Gy respectively whilst a recent review of 16 studies in patients with mediastinal HL reported average MHD, MLD and MBD of 11.4 Gy, 9.4 Gy and 4.4 Gy respectively.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, the potential benefit is variable and dependent on many factors including age, gender, tumor location, and patient-specific comorbidities. This specific radiation modality should be discussed on a "case-by-case" basis and, if found to be warranted, patients should be treated at PT facilities with sufficient expertise (41). At our facility, all lymphoma patients treated with PT are placed on a prospective registry study with long follow-up to investigate long-term toxicities like cardiac events or SM.…”
Section: Discussionmentioning
confidence: 99%
“…Voong et al (21) observed a reduction in heart dose (but not in breast dose) by using five to seven IMRT beams (butterfly) with eventually one non-coplanar beam, relative to 3D-CRT in patients without bilateral axillary involvement. Proton therapy has also been proposed for further reductions of late toxicity in selected lymphoma patients (17,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%